Epstein-Barr Virus–Associated Nodal Marginal Zone Lymphoma: Part of the Spectrum of Posttransplant Lymphoproliferative Disorder?. (February 2019) - Cheung, Chi Yuen; Lau, Wing Hung; Cheuk, Wah
A 56-year-old man, who received deceased kidney transplant 20 years ago, presented with an enlarged submandibular lymph node. Histologic examination revealed nodal marginal zone lymphoma in which the neoplastic lymphoid cells showed diffuse positivity for Epstein-Barr virus early RNA by in situ hybridization. Systemic lymphoma workup showed stage I disease. The tumor was managed as a posttransplant lymphoproliferative disorder and the immunosuppression was modified. There was no evidence of lymphoma at follow-up 6 years after excision alone. This case supports the inclusion of Epstein-Barr virus–positive nodal marginal zone lymphoma as a form of monomorphic B-cell lymphoproliferative disorder, in line with the status of its extranodal mucosa-associated lymphoid tissue lymphoma counterpart.